USING ANIMATED FILM TO DEVELOP SEVENTH GRADER’S DESCRIPTION WRITING SKILLS - Rahmawati, Na Stiti Tri; Sumardiyani, Listyaning; Nur’Aini, Siti (Universitas Muhammadiyah Palembang, 2025)
This research aims to determine whether animated films effectively overcome students' challenges when writing descriptive texts, particularly difficulties in expressing ideas. This study employs a qualitative descriptive methodology, with data collection conducted through observations, recording, test, and interviews. The data analysis method was descriptive analysis. The research involved 32 students of 7th grade at SMP N 42 Semarang over 2 hours. The findings reveal three main positive aspects: student enthusiasm, because animated films can attract attention and make the learning atmosphere more enjoyable. Second improved understanding of the film characters, the students can see the characters' expressions, actions, and personalities directly, making the character descriptions in their writing more accurate and vivid. Last increased motivation to write, animated films provide inspiration and new ideas for students. The students feel more motivated to write because they have clear and interesting visual references. This makes the writing process not feel boring, so students are more active and productive in producing written works. The researchers concluded that animated films can simplify writing descriptive texts by making learning materials more engaging and easier to understand.